The challenge fund aid modality: Assessing the potential for tackling gender challenges in development - Nilima Gulrajani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper compares the use of Challenge Funds by the UK's Department for International Development and Sweden's International Development Agency to address gender challenges in development. Challenges Funds are meant to bring the interests of business and donors together by stimulating innovative solutions to long-standing development problems. To date, the extent to which the Challenges Funds modality integrates donor commitments to gender has not been explored. This paper begins such an analysis by examining if, and how, two Challenge Funds - DfID's Business Innovation Facility and Sida's Innovations Against Poverty - are mainstreaming gender concerns along two dimensions. First, are robust gender criteria used to identify businesses that will be selected for Challenges Fund support? Second, how is performance of Challenges Fund investments assessed, and how are gender concerns integrated into these assessments? Findings indicate that in their current form, the Innovations Against Poverty offers a more robust focus on gender challenges than the Business Innovation Fund. Nevertheless, this should not instill over-confidence in either Challenge Fund to tackle complex structural development impediments to gender equality and women's empowerment. Policy makers must pay greater attention to the organization and management of donor-corporate partnerships if they want to make a lasting and sustainable contribution to development.
Keywords: O1; O2; O4; 330; foreign aid; challenge funds; gender; aid effectiveness; bottom of the pyramid; business and development